검찰과 법원의 민주적 조직정당성 확보에 관한 연구 : 텍스트 마이닝을 활용한 관련 언론기사 분석 - 유한별; Hanbyeol Yoo; 나태준; T. J. Lah (한국행정연구, 2021)
본 연구의 목적은 우리나라 검찰과 법원이 민주적 조직정당성을 확보하고 있는지 확인하는 데 있다. 검찰과 법원은 사법기관으로서의 소명을 다하기 위해 국민의사와 합치된 민주적 조직정당성의 확보가 당연시되고 있는 바, 실제 언론기사를 분석하여 이를 확보하고 있는지 확인하고자 하였다. 분석을 위해 검찰과 법원 관련 언론기사의 긍·부정적 이슈화를 통해 텍스트 마이닝을 활용하여 감성 분석, 워드 클라우드, 빈도 분석, 유사도 분석을 실시하였다. 연구 결과, 이 기관들은 정당성 확보에 실패하고 있는 것으로 확인되었으며, 사법기관에 대한 국민의 불신이라는 공공부채를 형성하고 있는 것으로 나타났다. The purpose of this study is to ensure that the prosecution service and court have democratic organizational legitimacy in Korea. With this study, it is to research for the prosecution and the court to secure democratic organizational legitimacy that is taken for granted in order to fulfill their call as judicial authorities. For aims of this study, we analyze actual media articles about the prosecution and the court. For analysis, it were conducted matching positive and negative issues of media articles related to the prosecution and the court using text mining with emotional analysis, word cloud, frequency analysis, and similarity analysis. it have confirmed for this study that judicial authorities fail to secure the legitimacy and are to form a public liabilities of public distrust of judicial authorities.